Effectiveness of long-term cluster training and traditional resistance training in enhancing maximum strength in young adults: a systematic review and meta-analysis - Cui, Jiayue; Yu, Yin; Xu, Yijun; Wu, Hongyu (Frontiers in Physiology, 2025)
BackgroundIt is still unclear whether traditional resistance training (TRT) provides the best or optimal stimulation for increasing maximum strength compared to cluster training (CT).ObjectiveThis study assessed the long-term impact of cluster training on the augmentation of maximum strength in young adults through the implementation of meta-analysis and further investigation of the factors associated with training duration.MethodLiterature was searched in Web of Science, Pub Med, EBSCOhost, SPORTDiscus, and Google Scholar. After screening, 21 articles and 49 reports were included. Revman 5.4 was used for literature quality evaluation, heterogeneity testing, and data consolidation. Stata 15.1 was used for drawing forest plots, subgroup analysis, taking sensitivity analysis and meta-regression to explore the sources of heterogeneity, creating a funnel plot to evaluate publication bias, quantifying publication bias, and trimming and filling. The original protocol was prospectively registered at the PROSPERO (CRD42024547097).ResultThe random effects meta-analysis results showed significant heterogeneity (I2 = 70.7%), SMD = 0.10, 95% confidence interval (CI) [-0.14, 0.33], indicating no difference between CT and TRT in general. However, considering training duration, CT was more effective in 4–8 weeks (SMD = 0.24, 95%CI [0.06, 0.42]), while TRT was better in 9–12 weeks (SMD = −1.54, 95%CI [-3.03, −0.05]). Sub-group analysis found that CT had a better effect on people aged 23 and above (SMD = 0.38, 95% CI [0.11, 0.65]), and there was no significant difference in sex and participant type.ConclusionCluster training (CT) mitigates exercise-induced fatigue more effectively than traditional resistance training (TRT) and enables more efficient maximum strength growth within the initial 8 weeks, however, the converse holds after 9 weeks. For preparation periods of 8 weeks or less, such as a microcycle or a specific stage in block periodization, trainers are advised to adopt CT for enhancing or maintaining maximum strength. This suggests that trainers, when undertaking maximum strength training, whether short-term or long-term, can not only consider CT but also precisely schedule the time-course of resistance training modalities within continuous periodization. Specifically, they can switch to TRT after 8-weeks of CT to achieve more favorable training outcomes.Systematic Review RegistrationPROSPERO